2013
DOI: 10.1179/1465313313y.0000000080
|View full text |Cite
|
Sign up to set email alerts
|

Does the British Orthodontic Society orthognathic DVD aid a prospective patient’s decision making? A qualitative study

Abstract: Objectives: To explore the views of potential orthognathic patients concerning the influence of the BOS Orthognathic DVD in their decision making process.Design: Qualitative, cross sectional study Setting: A UK dental teaching hospital Participants: Patients considering orthognathic treatmentMethods: New patients were recruited from orthognathic clinics following an initial consultation. After an appropriate time to view the DVD, in-depth interviews were conducted with 10 patients (aged 16-48yrs) in their home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“… Qualitative and quantitative / Semi-structured interviews / 7 / Adolescents / Adults The results showed that different facial angles and proportions of what is proposed as scientifically aesthetic does not interfere with the results of treatment, provided that the facial perception of the subjects involved meet the standards of normality and accepted by them and those set by society. Flett et al 16 (2014) / United Kingdom / Journal of Orthodontics Explore the views of potentially orthognathic patients considering the influence of a DVD about orthognathic surgery in the decision to perform the procedure. Qualitative / Unstructured interviews / 10 / Adolescents / Adults The DVD provided reliable information that patients do not get or cannot understand from professionals or the internet.…”
Section: Resultsmentioning
confidence: 99%
“… Qualitative and quantitative / Semi-structured interviews / 7 / Adolescents / Adults The results showed that different facial angles and proportions of what is proposed as scientifically aesthetic does not interfere with the results of treatment, provided that the facial perception of the subjects involved meet the standards of normality and accepted by them and those set by society. Flett et al 16 (2014) / United Kingdom / Journal of Orthodontics Explore the views of potentially orthognathic patients considering the influence of a DVD about orthognathic surgery in the decision to perform the procedure. Qualitative / Unstructured interviews / 10 / Adolescents / Adults The DVD provided reliable information that patients do not get or cannot understand from professionals or the internet.…”
Section: Resultsmentioning
confidence: 99%
“…This qualitative study investigated how patients at different stages of orthognathic treatment perceived "Your Jaw Surgery". In a review of a BOS DVD, Flett et al, (2014) found that the menu could cause confusion. In contrast the OIR was seen as easy to use, with a clear layout and information provided in a straightforward way.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of practical advice can encourage patients to seek information from other sources, such as Internet discussion boards, which can lead to patient confusion and dissatisfaction (Bhamrah et al, 2015). Flett et al, (2014) investigated how far a British Orthodontic Society (BOS) DVD helped patients to make decisions about orthognathic surgery. The DVD was felt to provide trusted information about orthognathic surgery however, there were some practical issues using the DVD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PDAs are increasingly used in medicine, they are not commonly used in dentistry [8][9][10][11] . This is despite research showing the need to consider patient values and preferences when making decisions about dental treatment and there is evidence that dental patients prefer a collaborative style of decision-making 12,13 .…”
Section: Introductionmentioning
confidence: 99%